Investigation and analysis of the practice environment of clinical nurses in a grade-A tertiary hospital of integrated traditional Chinese and western medicine (某三甲中西医结合医院临床护士执业环境调查分析) - XIONG Siqi (熊斯琪); LI Ronghua (李容华); DU Fang (杜芳); WANG Chaoqun (王超群) (Journal of International Translational Medicine Limited, 2021)
Objective To investigate the current status of nurses' practice environment in a grade-A tertiary integrated traditional Chinese and Western medicine hospital. Methods Use the "Nurse Practice Environment Evaluation Scale" to conduct a questionnaire survey on 520 nurses in the hospital. Results The average score was 77. 92(77. 92±10. 81) points. The item with highest score was 'systematic training program for newly recruited nurses', and the item with lowest score was 'nurse participation in the decision making of hospital affairs '. Conclusion Hospital managers need to provide nurses with more learning opportunities for communication and a platform for participating in hospital affairs decision-making, fully mobilize the enthusiasm of nurses to work, and further build a healthy nurse practice environment. (目的 了解某三甲中西医结合医院护士执业环境现状。方法 采用《护士执业环境测评量表》对院区376名护士进行问卷调查。结果 护士执业环境测评得分(77. 92±10. 81)分, "医院对新入职护士有系统培训"条目得分最高, "护士有机会参与医院内部管理"与"护士有机会决定医院事务"得分较低。结论 管理者需为护士提供更多学习交流的机会和参与医院事务决策的平台, 充分调动护士工作积极性, 进一步构建健康的护士执业环境。)